Glyphosate-based herbicides toxicity on life history parameters of zoophytophagous Podisus nigrispinus (Heteroptera: Pentatomidae) - Zanuncio, Jose C.; Lacerda, Mabio C.; Alcantara-de la Cruz, Ricardo; Brugger, Bruno P.; Pereira, Alexandre I. A.; Wilcken, Carlos F. [UNESP]; Serrao, Jose E.; Sediyama, Carlos S. (Elsevier B.V., 2018)
The increase of agricultural areas with glyphosate-resistant (GR) crops, and use of this herbicide in Brazil, makes necessary to assess its impacts on non-target organisms. The objective was to evaluate the development, reproduction and life table parameters of Podisus nigrispinus (Heteroptera: Pentatomidae) reared on GR-soybean plants treated with glyphosate formulations (Zapp-Qi, Roundup-Transorb-R and Roundup-Original) at the recommended field dose (720 g acid equivalent ha(-1)). Glyphosate formulations had no affect on nymph and adult weight of this predator. Fourth instar stage was shortest with Zapp Qi. Egg-adult period was similar between treatments (26 days) with a survival over 90%. Zapp-Qi and Roundup-Transorb-R (potassium-salt K-salt) reduced the egg, posture and nymph number per female, and the longevity and oviposition periods of this predator. Podisus nigrispinus net reproductive rate was highest in GR-soybean plants treated with Roundup-Original (isopropylamine-salt: IPA-salt). However, the duration of one generation, intrinsic and finite increase rates, and time to duplicate the population, were similar between treatments. Glyphosate toxicity on P. nigrispinus depends of the glyphosate salt type. IPA-salt was least harmless to this predator. Formulations based on K-salt altered its reproductive parameters, however, the development and population dynamic were not affect. Therefore, these glyphosate formulations are compatible with the predator P. nigrispinus with GR-soybean crop.
Keywords: Dynamic populations; Natural enemies; Pesticide side-effects; Predator; Stink bug; Risk assessment